2004
DOI: 10.1002/14651858.cd003177.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Omega 3 fatty acids for prevention and treatment of cardiovascular disease

Abstract: Background It has been suggested that omega 3 (W3, n-3 or omega-3) fats from oily fish and plants are beneficial to health. Objectives To assess whether dietary or supplemental omega 3 fatty acids alter total mortality, cardiovascular events or cancers using both RCT and cohort studies. Search methods Five databases including CENTRAL, MEDLINE and EMBASE were searched to February 2002. No language restrictions were applied. Bibliographies were checked and authors contacted. Selection criteria RCTs were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
144
2
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(154 citation statements)
references
References 258 publications
(389 reference statements)
4
144
2
4
Order By: Relevance
“…This trial has been criticized as being unblinded and for the nature of the EPA-rich fish oil (Marik and Varon, 2009). Hooper et al (2004) note that excluding this one trial alters the conclusions of the analysis and supports a beneficial effect of n-3 PUFA. A contemporary systematic review by Wang et al (2006) concluded that consumption of very long chain n-3 PUFA from fish or fish oil reduces overall mortality, cardiac mortality and sudden death, with the evidence being considerably stronger for secondary prevention (in subjects who have already suffered a CVD event) rather than primary prevention.…”
Section: Long Chain N-3 Pufa and Cvdmentioning
confidence: 88%
See 2 more Smart Citations
“…This trial has been criticized as being unblinded and for the nature of the EPA-rich fish oil (Marik and Varon, 2009). Hooper et al (2004) note that excluding this one trial alters the conclusions of the analysis and supports a beneficial effect of n-3 PUFA. A contemporary systematic review by Wang et al (2006) concluded that consumption of very long chain n-3 PUFA from fish or fish oil reduces overall mortality, cardiac mortality and sudden death, with the evidence being considerably stronger for secondary prevention (in subjects who have already suffered a CVD event) rather than primary prevention.…”
Section: Long Chain N-3 Pufa and Cvdmentioning
confidence: 88%
“…Such findings have spawned a large number of cohort and interventional studies aimed at evaluating the possible benefits of consuming very long chain n-3 PUFA (either through consuming fish or fish oil supplements) on CVD mortality and morbidity. Hooper et al (2004 and carried out a systematic review of 48 randomized control trials and 41 cohort studies investigating the impact of n-3 PUFA on total mortality and CVD events. Their somewhat surprising conclusion was that there was no clear evidence that dietary or supplemental n-3 PUFA altered total mortality or combined CVD events either in people with, or at high risk of, CVD or in the general population.…”
Section: Long Chain N-3 Pufa and Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…Omega-3 (n-3) polyunsaturated fatty acids (PUFA) are an alternative triacylglycerol-lowering therapy; there is strong epidemiological evidence suggesting favourable outcomes in people with type 2 diabetes with high omega-3 PUFA intake [16] and improvements in CVD-risk-factor profiles [17,18]. Studies involving wider populations have been less supportive [19], and a prospective primary-care trial is required to establish whether omega-3 PUFA, alone or with a statin, can improve risk-factor levels and reduce estimated CVD risk as a prelude to cardiovascular-outcome studies.…”
Section: Introductionmentioning
confidence: 99%
“…8.1 n-3 fatty acids Over the years, dietary n-3 fatty acids have gained a reputation in preventing and treating several disorders including cardiovascular diseases, rheumatoid arthritis and Alzheimer's disease by way of anti-inflammatory, antithrombotic, antiarrythmic, hypolipidemic and vasodilatory activities (101,(106)(107)(108)(109)(110)(111). It has been shown in human and animal studies that these n-3 fatty acids have potent immunomodulatory and anti-inflammatory effects by inhibiting the production of inflammatory mediators, eicosanoids, PGE2 and LTB4 and cytokines, TNF and IL1 (112).…”
Section: Novel Therapies For Ulcerative Colitismentioning
confidence: 99%